941 views
4 votes
Hi I really need help on how to solve this step by step as I am very confused. I figured out the first. I just need help on the second.

Hi I really need help on how to solve this step by step as I am very confused. I figured-example-1
User VeikkoW
by
4.4k points

1 Answer

5 votes

SOLUTION:

Case: Functions

Method:

a)

Given that:


\begin{gathered} f(x)=7x-5 \\ f\circ f(-1) \\ \Rightarrow f(-1)=7(-1)-5 \\ f(-1)=-7-5 \\ f(-1)=-12 \\ \Rightarrow f(f(-1)) \\ f(-12)=7(-12)-5 \\ f(-12)=-84-5 \\ f(-12)=-89 \end{gathered}

b)


\begin{gathered} g(x)=4-x^2 \\ g\circ g(4) \\ \Rightarrow g(4)=4-(4)^2 \\ g(4)=4-16 \\ g(4)=-12 \\ \Rightarrow g(g(4)) \\ g(-12)=4-(-12)^2 \\ g(-12)=4-144 \\ g(-12)=-140 \end{gathered}

Final answer:


\begin{gathered} a)f\circ f(-1)=-89 \\ b)g\circ g(4)=-140 \end{gathered}

User NARKOZ
by
5.4k points